Monitoring of Staphylococcus epidermidis biofilm formation on platelet storage bag surfaces - Jolianne Matte; Sahra Fonseca; Jonathan Robidoux; Steve J. Charette; Marie-Pierre Cayer; Danny Brouard (PLoS ONE, 2025)
Platelet concentrates (PCs) are stored at 20–24˚C in a biologically favorable environment that may support bacterial growth. Staphylococcus epidermidis , a typical contaminant, can form biofilms in PCs, complicating detection and increasing the risk of transfusion-transmitted bacterial infections. The material composition and surface texture of PC storage bags may influence biofilm formation. The impact of different PC storage bag materials on S. epidermidis biofilm formation was evaluated using the ISO 4768:2023(E) crystal violet (CV) assay. Four surface conditions were tested: polyvinyl chloride (PVC) plasticized with n-butyryl-tri(n-hexyl)-citrate (BTHC) – both smooth and rough sides, PVC plasticized with tri-(2-ethylhexyl)-trimellitate (TEHTM) and ethylene-vinyl acetate (EVA). Coupons and bags made from each material were used in the experiments. Biofilm-positive S. epidermidis was cultured in tryptic soy broth (TSB), PCs and plasma and added on plastic coupons under static conditions or directly in the bags with agitation. Bacterial enumeration and CV assay were performed on days 2, 5, and 7. In TSB, EVA coupons significantly formed more biofilm than the smooth side of PVC-BTHC or TEHTM over seven days. In PCs, more biofilm formed on the rough side of PVC-BTHC coupons than the smooth side, with no other differences between plastics, suggesting similar biofilm amount across PC bag materials in the presence of platelets. No biofilm was detected on coupons in plasma. Under continuous agitation and reduced oxygen levels, only the rough side of PVC-BTHC showed significant biofilm formation in TSB in PC storage bags over seven days. These findings highlight the need for standardized biofilm testing and suggest that some plastics are more conducive to biofilm formation under static conditions. However, during blood bank storage (i.e., continuous agitation and reduced oxygen levels), biofilm formation is limited, regardless of the platelet bag material, thereby reducing the risk of undetected bacterial contamination.